Um estudo sobre o impacto do tabagismo e alcoolismo no gasto público com saúde no Brasil - Bezerra, Diva Araripe (2015)
The Brazilian society views with astonishment the growth of alcohol dependence and smoking and the problems of biopsychosocial order resulting therefrom, which affect both the users themselves, as their families, causing high economic and social cost. In Brazil, although the consumption of alcohol and tobacco reaches a relevant population, it is still poorly researched the cost it entails for both the Unified Health System (SUS), as the social costs arising therefrom. The Ministry of Health has sought to confront this problem through a collective construction of Policy for Integral Attention to the Use of Alcohol and Other Drugs. This work aims to contribute to the assessment of the costs to health associated with alcohol and smoking from the perspective of the National Health System. Thus, for the purpose of this work will be considered the data and information provided by the information systems of federal agencies, state and municipal.